2000
DOI: 10.1038/sj.jhh.1001018
|View full text |Cite
|
Sign up to set email alerts
|

Hypertension in pregnancy

Abstract: Hypertension arising during pregnancy remains one of the two most frequently-cited causes of maternal death in the UK. In some cases, pregnancy is unmasking underlying hypertension, which manifests itself in later life. Pregnant women who develop de novo proteinuric hypertension (pre-eclampsia, PE) can share many risk factors with patients with the metabolic syndrome, such as obesity, dyslipidaemia and insulin resistance. However, more than half the women who develop PE remain normotensive thereafter. There is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(23 citation statements)
references
References 240 publications
(223 reference statements)
0
22
1
Order By: Relevance
“…Other genes currently under investigation are likely to be involved in GH and PE predisposition such as those associated with blood pressure control (Morgan and Ward 1999), thrombophilia (Kupferminc et al 2000;Ozcan et al 2001) and oxidative stress (Broughton Pipkin and Roberts 2000;Wang and Walsh 1996), but results are contradictory, possibly due to differences in study design, genetic heterogeneity of the disorder, the genetic background of the populations studied, as well as genetic stratification and type I error (GOPEC Consortium 2005). The French-Canadian population is characterized by a founder effect (Heyer and Tremblay 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Other genes currently under investigation are likely to be involved in GH and PE predisposition such as those associated with blood pressure control (Morgan and Ward 1999), thrombophilia (Kupferminc et al 2000;Ozcan et al 2001) and oxidative stress (Broughton Pipkin and Roberts 2000;Wang and Walsh 1996), but results are contradictory, possibly due to differences in study design, genetic heterogeneity of the disorder, the genetic background of the populations studied, as well as genetic stratification and type I error (GOPEC Consortium 2005). The French-Canadian population is characterized by a founder effect (Heyer and Tremblay 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Excessive activation of the maternal inflammatory response to these factors could affect the normal chorioplacental formation by both maternal and paternal genetic conflict. Broughton-Pipkin 35 reported that the risk of PE in women with a history of PE was reduced 30% after changing partner; however, women with a normal blood pressure during pregnancy who changed partner, had a 30% higher risk than those with the same partner.…”
Section: Genetic Causes Of Pementioning
confidence: 99%
“…A tendency to hypercoagulability predisposes women to PE 58 . It is reported that a polymorphism in the angiotensinogen gene is more frequent in women with PE than in normotensive pregnant women 59 . Several polymorphisms in genes that control the clotting cascade have also been identified, although the data linking particular polymorphisms to PE are contradictory, presumably due to the differences in the populations studied.…”
Section: Genetic Factorsmentioning
confidence: 99%
“…5 Placenta is a source and central of any mediators in preeclampsia pathogenesis. 6,7 Morever, placenta is also responsible in preeclampsia development, in which there is disturbance in placentation, poor invasion, and abnormal angiogenesis which is the main pathological manifestation. 7 These events are results from oxidative stress found in placenta in preeclampsia.…”
Section: Introductionmentioning
confidence: 99%
“…6,7 Morever, placenta is also responsible in preeclampsia development, in which there is disturbance in placentation, poor invasion, and abnormal angiogenesis which is the main pathological manifestation. 7 These events are results from oxidative stress found in placenta in preeclampsia. Studies show that soluble vascular endothelial growth factor receptor-1 (VEGFR-1) or known as soluble fms-like tyrosine kinase-1 (sFlt-1) and soluble endoglin (sEng), are mediator mechanism between ischemic placenta and oxidative stress with failure in local angiogenesis 8,9 , that leads to systemic vascular dysfunction.…”
Section: Introductionmentioning
confidence: 99%